Prevalence of Candida albicans and Trichomonas vaginalis Among Women of Childbearing Age in Wukari Metropolis, Taraba State - Andemi E. J.; Hemen A. I. J.; Ronald W. A. (African Journal of Medicine, Surgery and Public Health Research, 2026)
Vulvovaginal infections caused by Candida albicans and Trichomonas vaginalis remain important reproductive health concerns among women of childbearing age, yet epidemiological evidence from Wukari Metropolis is limited. This study examined the prevalence of C. albicans and T. vaginalis and their associations with sociodemographic, clinical, and behavioral factors among women of childbearing age in Wukari Metropolis. Vaginal swab specimens were collected from 163 consenting participants and examined macroscopically and microscopically, while C. albicans isolates were confirmed using the germ-tube test. No T. vaginalis infection was detected; therefore, subsequent analyses focused on C. albicans. The overall prevalence of C. albicans infection was 60.1%, with the highest prevalence recorded among women aged 40–49 years (100%) and the lowest among those aged 30–34 years (35.5%; χ² = 42.30, p < .001). Infection prevalence was significantly higher among women with informal education (86.4%) or primary education (87.9%) than among those with tertiary education (41.9%; χ² = 26.69, p < .001). Married women also had a higher prevalence than unmarried women (69.2% vs. 48.6%; χ² = 7.13, p = .008). Diabetes and HIV infection were important risk factors, with C. albicans detected in 100% of participants with diabetes and 75% of those living with HIV, yielding a combined prevalence of 91.3% (χ² = 4.11, p = .043). Significant clinical associations were observed for dyspareunia (80.2%), dysuria (69.7%), and vaginal discharge (52.4%; all p < .05). Self-medication was also significantly associated with infection (74.3%; χ² = 10.38, p = .006), as was the use of feminine hygiene products (χ² = 4.37, p = .037). These findings demonstrate a high burden of C. albicans infection despite the absence of T. vaginalis and highlight the influence of educational status, marital status, underlying health conditions, clinical symptoms, and personal health practices. The study provides locally relevant epidemiological evidence to support targeted screening, health education, and prevention strategies for vulvovaginal candidiasis among women of childbearing age in Wukari Metropolis.